Isotope-Disorder-Induced Line Broadening of Phonons in the Raman Spectra of SiC - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review Letters, 2001)
The linewidth of a phonon in isotopically disordered SiC was shown to be not depending on the degree of mass disorder but on the frequency of the phonons. The elastic scattering by mass fluctuations contributed to the linewidth and the scattering rate was proportional to the density of final phonon states.
UnivIS-Import:2015-04-14:Pub.2001.nat.dphy.IAP.LAP.isotop_54